The Influence of Tax Planning and Managerial Ownership on Company Value with Company Transparency as a Moderating Variable - Aulia, Triana Zuhrotun; Sudarmanto, Eko; Siregar, Indra Gunawan; Basuki; Pambudi, Januar Eky (International Journal of Sustainability in Research, 2024)
The scope of this study is to determine the effect of tax planning and managerial ownership on company value with companies transparency as a moderating variable in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX). The time period is 4 years, period is 2018-2021. The techniques used are techniques that are carried out intentionally. Based of the stability criteria is 8 companies were obtained. The data used is secondary data from the Indonesia Stock Exchange website. The analytical method used is regression analysis based on panel data. The research conclusion is that company value is not influenced by tax planning. Meanwhile, managerial ownership shows a negative influence on company value. Corporate transparency is not able to moderate the influence of tax planning on corporate value, and corporate transparency is able to moderate the influence of managerial ownership on corporate value.